2017
DOI: 10.1007/s00737-017-0807-9
|View full text |Cite|
|
Sign up to set email alerts
|

Stigma in the context of pregnancy termination after diagnosis of fetal anomaly: associations with grief, trauma, and depression

Abstract: Termination of pregnancy after diagnosis of fetal anomaly (TOPFA) is a contested issue and stigma may negatively impact affected women's psychological reactions. This study examined the influence of perceived and internalized stigma on women's long-term adjustment to a TOPFA. One hundred forty-eight women whose TOPFA dated back 1 to 7 years responded to self-report questionnaires. The associations between perceived stigma at the time of the TOPFA, current internalized stigma and symptoms of grief, trauma and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Research showed that women do not reveal the information of pregnancy termination for fear of social stigmatization [2,20]. Studies conducted in Germany demonstrated that patients living in the eastern region, which is more liberal than the western one, reported a lower sense of being stigmatized [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that women do not reveal the information of pregnancy termination for fear of social stigmatization [2,20]. Studies conducted in Germany demonstrated that patients living in the eastern region, which is more liberal than the western one, reported a lower sense of being stigmatized [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…All data were collected in a cross-sectional study using self-administered questionnaires and database information taken from the register of the Department of Obstetrics (University of Leipzig). Details of the same study pertaining to the methods and the sample characteristics have been published elsewhere [ 28 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies involving women who had had abortions after diagnosis of fetal anomaly, due to an unintended pregnancy or for other reasons have linked stigma to women’s need to keep the abortion a secret, increased psychological distress and somatic symptoms [ 24 28 ]. The vast literature on other stigmatized conditions (i.e., obesity or mental illness) suggests additional negative consequences of abortion stigma for women’s well-being, such as impaired self-esteem [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, few terminations are performed in Poland due to the above maternal indications. Sociodemographic factors such as age, other children, ethnic origin, religion, educational background, marital status, profession, views on abortion, and relations with partners have various impacts on the decision to undergo abortion, depending on the research methodology, country and reasons for making the decision to terminate the pregnancy [4,5,6,7]. Moreover, numerous external factors influence the process of making a decision about termination of a pregnancy: legislation, the healthcare system, scope of medical insurance, access to healthcare services, activity of support groups, social position and access to medical information [8,9].…”
Section: Introductionmentioning
confidence: 99%